(untitled) (Research, Society and Development, 2024)
Ankylosis of the temporomandibular joint (TMJ) occurs when the condyle-disk complex joins the articular surface of the temporal bone, resulting in an anatomical-functional alteration. Its etiology is multifactorial, with trauma associated with condylar fracture being the most common cause. This condition results in various functional problems, including limited mouth opening and reduced chewing capacity in affected patients. Diagnosis is established by correlating clinical and imaging findings, enabling an accurate assessment and guiding therapeutic decisions. Currently, various surgical modalities are used to treat TMJ ankylosis, including gap arthroplasty, interpositional arthroplasty, joint reconstruction and osteogenic distraction. With this in mind, this paper aims to present and analyze the different surgical interventions used to treat TMJ ankylosis, offering a concise overview of the possible forms of treatment. To develop this article, searches were carried out in the Google Scholar, PubMed and SciELO databases. The study covered works published between 2013 and 2023 in Portuguese, English and Spanish. This review highlighted the various techniques available to address TMJ ankylosis. However, controversies persist regarding the standard method of treatment, with no clear consensus among researchers. Regardless of the technique adopted, it is essential that treatment not only relieves symptoms, but also restores the functionality of the stomatognathic system and reduces the risk of reankylosis.